Understanding statistics with SPSS a friendly approach - Halilah Haron (Universiti Publication Centre (UPENA), 2010)
The topics selected in "Understanding Statistics with SPSS: A Friendly Approach" should be of interest to students and most researchers especially those from the social sciences. Students at the tertiary level and researchers with little knowledge in statistics should find this book very useful.